2016
DOI: 10.1016/j.memsci.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of nanoporous polyethersulfone membrane as support for composite membrane in CO2 separation: From lab to pilot scale

Abstract: Nanoporous polyethersulfone (PES) membranes were prepared from PES/N-methyl-2pyrrolidone (NMP)/2-methoxyethanol (2-ME) casting solutions with water as coagulant by both vapor-and non-solvent-induced phase inversion steps successively under various preparation parameters. 2-ME was incorporated into the casting solution as a pore-forming additive because of its high affinity with water, leading to more open membrane morphology. A detailed study of the effects of different parameters, including polymer concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 47 publications
(99 reference statements)
0
15
0
Order By: Relevance
“…During this step, the mass transfer and exchange rate of solvent/non‐solvent decrease and different membrane morphologies can be obtained . Some researchers have studied the effect of VIPS condition on the membrane morphology and performance . It has been demonstrated that by the using of VIPS technique, the formation of macrovoids is suppressed and typical symmetric spongy‐like morphology with cellular structure can be obtained.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…During this step, the mass transfer and exchange rate of solvent/non‐solvent decrease and different membrane morphologies can be obtained . Some researchers have studied the effect of VIPS condition on the membrane morphology and performance . It has been demonstrated that by the using of VIPS technique, the formation of macrovoids is suppressed and typical symmetric spongy‐like morphology with cellular structure can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Another strategy to alter the mass transfers of phase separation process and control the membrane morphology is addition of non‐solvent in the casting solution . In the presence of non‐solvent additive, the surface properties and porosity of the membrane can be improved . Li et al pointed out that the addition of a low molecular weight non‐solvent such as diethylene glycol can reduce the precipitation rate and create membrane with spongy‐like structure instead of macrovoid morphology .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, PES, which has an excellent separation performance and high thermal, chemical, hydraulic and mechanical stability, has been used in a wide range of membrane applications. [27][28][29][30] Furthermore, it can be used achieve asymmetric structures with various pore size ranges by controlling the chemical and physical conditions applied in the phase inversion process. The most important and effective parameters in the fabrication of NF membranes are polymer concentration, type of solvent and non-solvent, pore-forming agent, temperature of the coagulation bath and solvent evaporation time.…”
Section: Introductionmentioning
confidence: 99%